2002
DOI: 10.1191/0267659102pf588oa
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body hyperthermia: a review of theory, design and application

Abstract: The intentional induction of elevated body temperature to treat malignant lesions has its origins in the 18th century. The mechanism of heat-induced cell death is not clear; however, heat induces a variety of cellular changes. For heat to exert a therapeutic effect, pathogens (bacteria, viruses, or neoplastic tissues) need to be susceptible within temperature ranges that do not exert deleterious effects on normal tissues. Hyperthermia has been used successfully to treat isolated neoplastic lesions of the head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Unfortunately, "extreme" whole body hyperthermia (.41.5°C), which elevates core temperatures to the level where direct thermal toxicity is observed, can cause severe side effects, which may limit its usefulness. [4][5][6][7][8] Fever-level whole body hyperthermia (∼39°C-41°C) can mitigate many of these side effects and has potential to be an effective cancer treatment, but this lower heat level is thought, primarily, to stimulate the immune system and the benefits of direct thermal toxicity are reduced. 9,10 Generating localized hyperthermia at the cancer site could alleviate many of the side effects associated with whole body hyperthermia while still taking advantage of the thermal susceptibility of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, "extreme" whole body hyperthermia (.41.5°C), which elevates core temperatures to the level where direct thermal toxicity is observed, can cause severe side effects, which may limit its usefulness. [4][5][6][7][8] Fever-level whole body hyperthermia (∼39°C-41°C) can mitigate many of these side effects and has potential to be an effective cancer treatment, but this lower heat level is thought, primarily, to stimulate the immune system and the benefits of direct thermal toxicity are reduced. 9,10 Generating localized hyperthermia at the cancer site could alleviate many of the side effects associated with whole body hyperthermia while still taking advantage of the thermal susceptibility of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of blood circulation into the heat exchanger, it is easy to control and monitor the temperature [87]. The ongoing Phase I study in advanced non-small-cell lung cancer patients approved by the US FDA has shown its safety and effectiveness [88][89][90][91][92][93]. Several therapeutic effective strategies of heat in combination with other antineoplastics have been developed in this platform as shown in Figure 7a.…”
Section: Extracorporeal Circuitmentioning
confidence: 97%
“…Actually, the rich network of vessels absorbs bigger proportion of heat than compartment average if the equal amount of heat is imposed from outside. The unexpected systemic thermal responses reported during clinical practice in a regional hyperthermia [27,28] indicate the need of both description of remote temperature responses and the utilization of these effects. Given that 20 W heat is irradiated from skin surface, the heat absorbed by blood will be 6 W for systemic [15], the same as the compartment calculation.…”
Section: Systemic Thermal Response By Heating In Hands and Feetmentioning
confidence: 99%